DocTalk: Extending Doctors' Reach with Personalized Voice Messages - Ramkrishnan, Pranav; Vashistha, Aditya; Cutrell, Ed; Thies, Bill (ACM Symposium on Computing for Development (ACM DEV), 2013)
Because doctors are scarce in developing regions, they often lack the time to provide detailed counseling to every patient. In this paper, we propose DocTalk: a system that extends doctors' visits by allowing them to share pre-recorded audio messages, in their own voice, to patients with low-end mobile phones. DocTalk uses a combination of SMS and interactive voice response (IVR) to orchestrate this communication between doctors and patients. We describe the design and implementation of the system, as well as feedback gathered in conversations with 21 doctors in urban India.